Nerve Conduction Study in Healthy Individuals: a Gender Based Study (Health Renaissance, 2011)
Background: Nerve conduction study (NCS) assesses peripheral nerve functions and has clinical implication. Objective: To study effect of gender on NCS variables in healthy adults. Settings and Design: Department of Physiology, B.P. Koirala Institute of Health Sciences, Dharan, Nepal. Material and Method: The study was done in 34 (m=19, 32±11 years; f=15, 32±12 years) consenting healthy adults. The compound muscle action potential (CMAP) and sensory nerve action potential (SNAP) were recorded. Statistical analysis: The effect of gender on NCS variables was analyzed using Mann Whitney U test. Results: Male vs. female: males had increased CMAP and F-wave latencies (ms) in all tested motor nerves. CMAP duration (ms) was longer in males (p